DIGITAL EDUCATIONAL ENVIRONMENT AS A SYSTEM-FORMING ELEMENT OF DIGITAL DIDACTICS - Sagan, Olena; Nahrybelniy, Yaroslav; Nahrybeina, Inna; Fediaieva, Valentyna; Liba, Natalia; Kabelnikova, Natalia (Revista Inclusiones, 2020)
Digitization in education is one of the most actual issues in modern society. COVID-19 pandemic and connected with it lockdown showed the necessity of an urgent transition of educational processes of different levels to a mixed or distant education. Such changes in paradigm do not suggest the digitalization of the traditional content, but the creation of an educational system based on digital didactic principles. The article deals with the problem of designing, creation and testing of digital educational environment. The analysis of the researches enables to define the notion ‘digital educational environment’ and identify its components. The conducted questionnaire of 132 university and college teachers in Ukraine, who provided distant education during COVID-19 lockdown, demonstrated a positive qualitative increase of motivation criterion for the formation and application of all the components of digital educational environment, and allowed to identify the main problems, tackling of which is possible due to synergy of the state, science and system of education.